2010
DOI: 10.1161/hypertensionaha.110.158931
|View full text |Cite
|
Sign up to set email alerts
|

Plasma From Preeclamptic Women Increases Blood-Brain Barrier Permeability

Abstract: Abstract-Circulating factors in preeclamptic women are thought to cause endothelial dysfunction and thereby contribute to the progression of this hypertensive condition. Despite the involvement of neurological complications in preeclampsia, there is a paucity of data regarding the effect of circulating factors on cerebrovascular function. Using a rat model of pregnancy, we investigated blood-brain barrier permeability, myogenic activity, and the influence of endothelial vasodilator mechanisms in cerebral vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
94
2
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 33 publications
9
94
2
8
Order By: Relevance
“…A recent study demonstrated an increased blood-brain barrier permeability of 6.5-and 18-fold when exposed to normal pregnant (median of 34 weeks gestation) plasma and pre-eclamptic plasma, respectively. 16 With a combination of pathologic and potentially physiologic changes, it seems likely that the penetration of rituximab to the CNS lymphoma in our patient greatly exceeded that previously reported in the literature, despite a suggestion by some that dexamethasone can decrease the permeability of the blood-brain barrier. This is supported by the dramatic and immediate response experienced by our patient after experiencing progressive symptoms during treatment with highdose corticosteroids.…”
contrasting
confidence: 69%
“…A recent study demonstrated an increased blood-brain barrier permeability of 6.5-and 18-fold when exposed to normal pregnant (median of 34 weeks gestation) plasma and pre-eclamptic plasma, respectively. 16 With a combination of pathologic and potentially physiologic changes, it seems likely that the penetration of rituximab to the CNS lymphoma in our patient greatly exceeded that previously reported in the literature, despite a suggestion by some that dexamethasone can decrease the permeability of the blood-brain barrier. This is supported by the dramatic and immediate response experienced by our patient after experiencing progressive symptoms during treatment with highdose corticosteroids.…”
contrasting
confidence: 69%
“…In addition, hydraulic conductivity, an important parameter that relates water movement through the vessel wall in response to hydrostatic pressure, is normally very low in cerebral endothelial cells due to the high electrical resistance tight junctions and low pinocytotic activity (72). Similar to paracellular and transcellular permeability, hydraulic conductivity is not changed during pregnancy (24) but is increased in response to preeclamptic plasma (2). Increased hydraulic conductivity during preeclampsia could promote neurological symptoms since increased BBB permeability has been linked to several pathological states, including preeclampsia and eclampsia, as well as epilepsy (55,56,63).…”
Section: The Cerebral Endothelium and Bbbmentioning
confidence: 99%
“…For example, vascular endothelial growth factor (VEGF), a cytokine originally named vascular permeability factor, is secreted by the placenta and elevated during pregnancy in the uteroplacental unit and the maternal circulation (2,14,19,37). VEGF interacts with its receptors VEGFR1 [or FMS-like tyrosine kinase receptor 1 (Flt-1)] and VEGFR2 [or fetal liver kinase 1 (Flk-1)] located on vascular endothelium to initiate several critical physiological processes involved in angiogenesis, vascular growth, and endothelial cell survival (34,76).…”
Section: The Cerebral Endothelium and Bbbmentioning
confidence: 99%
“…However, their results cannot be extrapolated to preeclamptic patients as magnesium transfer to the CSF might differ in pre-eclampsia. One may postulate that pre-eclamptic changes in vascular permeability might allow magnesium to cross the blood brain barrier (8), but there are few reports exploring that theory. In their study comparing CSF magnesium levels in healthy and pre-eclamptic parturients not receiving magnesium therapy, Fong et al (10) did not find any difference.…”
Section: Discussionmentioning
confidence: 99%